2018
DOI: 10.1007/s12192-018-0936-8
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid induces human osteoblast-like Saos-2 cell apoptosis via endoplasmic reticulum stress and autophagy

Abstract: Palmitic acid (PA) is the most common saturated long-chain fatty acid in food that causes cell apoptosis. However, little is known about the molecular mechanisms of PA toxicity. In this study, we explore the effects of PA on proliferation and apoptosis in human osteoblast-like Saos-2 cells and uncover the signaling pathways involved in the process. Our study showed that endoplasmic reticulum (ER) stress and autophagy are involved in PA-induced Saos-2 cell apoptosis. We found that PA inhibited the viability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 63 publications
6
32
0
2
Order By: Relevance
“…GRP78 is an ER stress-response protein, and its expression is a typical marker of ER stress activation. Our previous results showed that PA triggers ER stress and then induces apoptosis though CHOP activation in Saos-2 cells [18]. In addition, this result is consistent with the results of other studies that showed that PA induces ER stress and apoptosis in hepatoma cells [35] and myocardial cells [34].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…GRP78 is an ER stress-response protein, and its expression is a typical marker of ER stress activation. Our previous results showed that PA triggers ER stress and then induces apoptosis though CHOP activation in Saos-2 cells [18]. In addition, this result is consistent with the results of other studies that showed that PA induces ER stress and apoptosis in hepatoma cells [35] and myocardial cells [34].…”
Section: Discussionsupporting
confidence: 91%
“…The cells were analyzed using a fluorescence-activated cell sorter (Becton, Dickinson and Company, USA) within 1 h of staining. The proportion of early apoptotic cells was determined by measuring the percentage of Annexin V+/PI− cells; the proportion of progressed apoptotic cells was obtained by determining the percentage of Annexin V+/PI+ cells; the proportion of necrotic cells was detected by determining the percentage of Annexin V−/PI+ cells and Annexin V−/PI− cells were considered surviving cells as previously reported [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested that increased ROS activate various signaling pathways, resulting in DNA damage and apoptosis [13,14]. Previous studies have also shown that oxidative and ER stresses are closely related [15,16]. Both oxidative stress [21] and ER stress [9] are involved in PA-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…To dissect the effects of altered lipid metabolism from other metabolic derangements in these models, in vitro culture systems wherein cultures of primary osteoblasts or osteoblast-like cell lines are treated with exogenous lipids have proven helpful (124,(135)(136)(137)(138)(139). The common finding in these studies is that the exposure to sufficient quantities of cholesterol, palmitate or oxidized LDL [a product of LDL interaction with reactive oxygen species (140)] reduces the proliferation of osteoblastic cells, induces cell death, and impairs osteoblast differentiation.…”
Section: Effect Of Dyslipidemia On Bone Structure and Remodelingmentioning
confidence: 99%